Crowe's Fraud Pentagon Theory Review Of Fraudulent Financial Statements With Audit Committee Moderation - Wulan Retnowati; T, Sutrisno; Saraswati, Erwin; Andayani, Wuryan (Accounting Department,, 2024)
Purpose—This study aims to analyze the Pentagon fraud theory for detecting fraud in financial statements, with the audit committee as a moderating variable. Design/methodology/approach — This study's population is manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The research sample is 198, comprising 66 company annual reports for three years. The analysis technique used in this study is multiple linear regression and uses the MRA (Moderating Regression Analysis) method through IBM SPSS version 26 software. Findings—The results showed that the variables of pressure and arrogance influenced fraud in financial statements, while the variables of opportunity, rationalization, and competence did not. The pressure and opportunity variables affect fraud in financial statements after being moderated by the audit committee variable, while the rationalization, competency, and arrogance variables have no effect. Practical implications — Practical benefits for stakeholders as a source of information regarding factors that can be detected as a cause of fraud in financial statements. That is expected to avoid or minimize fraud and fraudulent financial statements, which can later develop and harm many parties, especially business people. Originality/value — The difference between this study and previous research lies in using variables, research objects, research periods, and measurements that previous researchers have not carried out. Paper type — Research paper